Control of clinical paratuberculosis in New Zealand pastoral livestock. Issue 1 (2nd January 2018) - Gautam, M; Ridler, A; Wilson, PR; Heuer, C
Abstract: This review summarises current control measures for clinical paratuberculosis (Johne's disease; JD) in New Zealand pastoral livestock. Most New Zealand sheep, deer, beef and dairy cattle herds and flocks are infected by Mycobacterium avium ssp. paratuberculosis ( Map ). Dairy cattle and deer are mostly infected with bovine (Type II), and sheep and beef cattle with ovine (Type I) strains. Control in all industries is voluntary. While control in sheep and beef cattle is ad hoc, the dairy and deer industries have developed resources to assist development of farm-specific programmes. The primary target for all livestock is reduction of the incidence rate of clinical disease rather than bacterial eradication per se . For dairy farms, a nationally instituted JD-specific programme provides guidelines for risk management, monitoring and testing clinically suspect animals. While there is no formal programme for sheep farms, for those with annual prevalences of clinical disease >2%, especially fine wool breeds, vaccination may be a cost effective control option. The deer industry proactively monitors infection by a national abattoir surveillance programme and farmers with an apparent high disease incidence are encouraged to engage with a national network of trained consultants for management and control advice. Evaluation of the biological and economic effectiveness of control in all industries remains to be undertaken. Nevertheless, opportunities exist for farmers, who perceive significant JD problems in their herds/flocks, to participate in systematic best-practice activities that are likely to reduce the number of clinical infections with Map on their farms, and therefore the overall prevalence of JD in New Zealand's farming industries.